First report of a fish kill episode caused by pyrethroids in Italian freshwater. (December 2017) - Bille, Laura; Binato, Giovanni; Gabrieli, Claudio; Manfrin, Amedeo; Pascoli, Francesco; Pretto, Tobia; Toffan, Anna; Dalla Pozza, Manuela; Angeletti, Roberto; Arcangeli, Giuseppe
Highlights: A fish kill episode involving several species was investigated and described. Relevant concentrations of pyrethroids were detected both in water and fish tissues. This study represents the first Italian reported case of a pesticides-related fish kill. Abstract: Introduction: Fish kills are events of strong emotional impact on the population because of the frequent suspicion that they can be the result of serious pollution accidents. As a matter of fact, they are often due to natural occurrences, such as low levels of dissolved oxygen in the water, but in many cases the causes remain unknown. Fish are particularly sensitive to pesticides and pyrethroids are reported to be the most ecotoxicologically active in the aquatic environment. Nevertheless, the reported cases of massive wild fish mortalities due to these toxicants are very few. This paper describes a fish kill episode occurred in the Padua Province (Veneto Region — North Eastern Italy) which involved several fish species and for which it was possible to identify the cause in the presence of pyrethroids in the water. Case presentation: When a whitish liquid coming from the rainwater drain of an industrial area was seen to be spilling into a drainage channel, a fish massive mortality was noticed and investigated. The collected water samples showed the presence of relevant concentrations of cypermethrin, permethrin, deltamethrin and tetramethrin. Analyses on the fish tissues revealed the presence of cypermethrin and permethrin at a concentration range of 476–2834 μg/kg and 346–2826 μg/kg on a lipid basis, respectively. Discussion: According to the results of the performed analyses, we can reasonably state that the described episode had been caused by the exposure of biota to high concentrations of pyrethroids. The present case report significantly contributes to the limited literature available on pesticides-related fish kills. Moreover, it highlights the importance of sharing protocols for fish kill management at a national level, as this would help to better define the roles of the different institutions involved and to improve the investigation and the reporting of these events.